2022
DOI: 10.1007/s40272-022-00536-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of the Adjuvant Use of Probiotic Bacillus clausii Strains in Pediatric Irritable Bowel Syndrome: A Randomized, Double-Blind, Placebo-Controlled Study

Abstract: Objectives Current irritable bowel syndrome (IBS) treatments have limited efficacy and probiotics like Bacillus clausii ( B. clausii ) were found to be effective in the management of several gastrointestinal disorders. This phase III trial assessed the efficacy and safety of adding B. clausii (four strains: O/C, N/R, SIN, T), versus placebo, to conventional treatment of pediatric IBS in Mexico. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Full-text screening was conducted in the remaining 150 articles. We identified 46 studies of probiotic therapy in IBS [16–59], three studies of prebiotics [60–62] and three studies of synbiotics [63–65]. Finally, 50 articles reporting 52 studies were included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Full-text screening was conducted in the remaining 150 articles. We identified 46 studies of probiotic therapy in IBS [16–59], three studies of prebiotics [60–62] and three studies of synbiotics [63–65]. Finally, 50 articles reporting 52 studies were included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Therapeutic dosage of probiotics for each study was extracted for further analysis, and we only included studies reporting probiotic dosage in c.f.u. or that could be converted into c.f.u./day [17, 18, 21, 22, 25, 28, 34–47, 51, 52, 55, 56, 59] (). Trials, in which the dosages of probiotics were changed during the intervention period were excluded from the subgroup analysis [23, 24, 32, 33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found a significant decrease in the severity of abdominal pain with probiotic use, especially if the treatment duration exceeded 4 weeks [17 ▪ ]. Although the study by Vazquez-Frias et al [16 ▪ ] did not show any significant benefit of probiotics when compared with placebo, they still found that most of the patients treated with probiotics had symptom improvement. Additionally, the meta-analysis by Fatahi et al [17 ▪ ] showed that probiotic supplementation has the potential to reduce abdominal pain in patients with IBS.…”
Section: Treatment and Managementmentioning
confidence: 93%
“…This was in addition to conventional treatment such as diet, laxatives, analgesics, and antispasmodics. They found that 73.6% of participants in the treatment group and 78.5% of participants in the placebo group had clinical improvement in symptoms [16 ▪ ]. In another study, Fatahi et al conducted a systematic review and meta-analysis of RCTs as far back as April 2021 to evaluate the effectiveness of probiotic supplementation on abdominal pain severity in IBS, which included seven RCTs, totaling 441 participants.…”
Section: Treatment and Managementmentioning
confidence: 99%